Technical Report: Measuring the impact of low back pain in two population-based cohort studies of young and middle-aged adults - Coenen, Pieter; Smith, Anne; O’Sullivan, Peter; Beales, Darren; Straker, Leon (Curtin University, 2017)
Objective: Low back pain (LBP) places a large burden on society through health professional services and medication use, and interferences with work, normal and physical activities. Widely used and accepted questionnaires for measuring the impact of musculoskeletal pain (including LBP) exist, but do not cover all these aspects and may be too lengthy for some epidemiologic research and clinical practice settings. We evaluated the use of five single items of LBP impact on professional service, medication, and interferences with work, normal and physical activities; and compared these five items against established validated questionnaires of LBP disability and multi-dimensional screening of pain disability. Methods: We performed cross-sectional analyses of two population-based cohorts (with young adults and middle-aged adults). In both cohorts, LBP (Nordic questionnaire) and LBP impact (using the proposed five single items) were assessed. Validated questionnaires for multi-dimensional screening of long-term musculoskeletal pain disability (Orebro Musculoskeletal Pain Questionnaire) for young adults and LBP disability (Oswestry Disability Index) for middle-aged adults were used. Results: In both cohorts, participants who reported LBP with impact on the proposed items displayed higher scores on validated questionnaires compared to those reporting LBP without impact. Number of LBP impacts increased with increasing scores on validated questionnaires and showed high predictive value. The five proposed items of LBP impact are able to distinguish people with different clinically important scores (from established questionnaires), showing their construct validity. Conclusion: The described items provide a relevant and feasible tool to establish LBP impact in epidemiological research and clinical practice.